1075 THE EFFECTIVENESS OF INTERVENTIONS TO REDUCE ADVERSE OUTCOMES AMONG OLDER ADULTS FOLLOWING EMERGENCY DEPARTMENT DISCHARGE. (14th June 2022) - Conneely, M; Leahy, S; Dore, L; Trépel, D; Robinson, K; Jordan, F; Galvin, R
Abstract: Background: Population ageing is increasing rapidly worldwide. Older adults are frequent users of health care services including the Emergency Department (ED) and experience a number of adverse outcomes following an ED visit. Adverse outcomes include functional decline, unplanned hospital admission and an ED revisit. Given these adverse outcomes a number of interventions have been examined to improve the outcomes of older adults. The aim of this umbrella review was to evaluate the effectiveness of ED interventions in reducing adverse outcomes in older adults discharged from the ED. Method: Systematic reviews of randomised controlled trials investigating ED interventions for older adults presenting to the ED exploring clinical, patient experience and healthcare utilisation outcomes were included. A comprehensive search strategy was employed in eleven databases and grey literature was searched. Quality was assessed using the A MeaSurement Tool to Assess Systematic Reviews 2 tool. Overlap between systematic reviews was assessed and an algorithm to assign the Grading of Recommendations Assessment, Development and Evaluation to assess the strength of evidence was applied to outcomes. Results: Nine systematic reviews including 29 randomised controlled trials were included. Interventions comprised of solely ED-based or transitional interventions. The specific interventions delivered were highly variable. There was high overlap and low methodological quality of the trials informing the systematic reviews. There is low quality evidence to support ED interventions in reducing functional decline, improving patient experience and improving quality of life. The quality of evidence of the effectiveness of ED interventions to reduce mortality and ED revisits varied from very low to moderate. Conclusion: Older adults are the most important emerging group in healthcare for several economic, social and political reasons. The evidence for the effectiveness of ED interventions for older adults is limited. Higher quality intervention studies in line with current geriatric medicine research guidelines are recommended.